1998
DOI: 10.1016/s0092-8674(00)81608-6
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Adaptor Protein Orchestrates Receptor Patterning and Cytoskeletal Polarity in T-Cell Contacts

Abstract: Recognition of antigen by T cells requires the formation of a specialized junction between the T cell and the antigen-presenting cell. This junction is generated by the recruitment and the exclusion of specific proteins from the contact area. The mechanisms that regulate these events are unknown. Here we demonstrate that ligand engagement of the adhesion molecule, CD2, initiates a process of protein segregation, CD2 clustering, and cytoskeletal polarization. Although protein segregation was not dependent on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
606
0
8

Year Published

1999
1999
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 659 publications
(650 citation statements)
references
References 46 publications
29
606
0
8
Order By: Relevance
“…CD48iGFP thus reported CD2-driven accumulation of CD2/CD48 at the T cell-APC interface. Using human T cell clone-APC combinations or murine primary T cells on supported lipid bilayers as APC substitutes, accumulation of CD2/CD48 has previously been demonstrated, whether in a central pattern or spread over the interface (11,25).…”
Section: Cd2/cd48 Accumulates At the T Cell-apc Interfacementioning
confidence: 99%
“…CD48iGFP thus reported CD2-driven accumulation of CD2/CD48 at the T cell-APC interface. Using human T cell clone-APC combinations or murine primary T cells on supported lipid bilayers as APC substitutes, accumulation of CD2/CD48 has previously been demonstrated, whether in a central pattern or spread over the interface (11,25).…”
Section: Cd2/cd48 Accumulates At the T Cell-apc Interfacementioning
confidence: 99%
“…Subsequent (within minutes) to specific interactions of T cells with APCs, TCR and MHC molecules are assembled at the centre of supramolecular activation clusters at the site of T cell contact (2,(45)(46)(47). TCR-down-regulation is observed following interactions of TCR with pMHC complexes (48)(49)(50) and T cell-APC interactions cause APC-derived surface molecules to adhere to the surface of T cells (51,52).…”
Section: Tcr-mediated Internalization and Recyclingmentioning
confidence: 99%
“…The proline-rich region contains multiple PXXP sequences which are possible SH3 domainbinding sites [49]. Further, it was revealed that CIN85 shares significant sequence identity with CMS [50] and CD2AP (a mouse homologue of CMS) [51], with overall 36 and 38% identity in amino acid sequence, respectively. The primary structures of these three proteins are also quite similar to one another.…”
Section: Characteristic Features Of the Cin85 Proteinmentioning
confidence: 99%